Validity and stability of a computerized metabolic system with mixing chamber - Foss, O.; Hallen, J. (International Journal of Sports Medicine, 2005)
The aim of this study was to validate a computerized metabolic system with mixing chamber (Oxycon Pro, Erich Jaeger GmbH, Hoechberg, Germany) against the Douglas bag method (1) over a large range of ventilations and (2) for drift during shorter (25-min time trial) and longer (~ three months) test periods. Eighteen well-trained/elite cyclists performed graded exercise tests, maximal oxygen uptake tests and time trial tests on an electromagnetic braked cycle ergometer. Respiratory variables were measured simultaneously, once or several times in every test by the Oxycon Pro and the Douglas bag method. (1) Overall, oxygen uptake was 0.8 % (0.03 l · min-1) lower with the Oxycon Pro than with the Douglas bag method with a coefficient of variation of 1.2 % (n = 802) (p < 0.05). (2) During the time trials, oxygen uptake measured with the Oxycon Pro gradually decreased from 0.5 % (0.02 l) lower than the Douglas bag method at 5 min to 1.0 % (0.05 l) lower at 25 min (p < 0.05). Over the period of three months of testing, oxygen uptake measured with the Oxycon Pro gradually increased from 1.1 % (0.04 l) lower than the Douglas bag method at the start to 0.5 % (0.02 l) lower at the end (p < 0.05). This study demonstrates that a computerized metabolic system with mixing chamber is an accurate system for measuring oxygen uptake. This applies to testing over a large range of ventilations and for stability both during shorter and longer test periods.